2006
DOI: 10.1111/j.1365-2672.2005.02754.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological mutants of Gibberella fujikuroi for enhanced production of gibberellic acid

Abstract: Aims:  To examine the production of gibberellic acid by selected morphological mutants of Gibberella fujikuroi in liquid cultures. Methods and Results:  Mutants of G. fujikuroi having different morphological characteristics were selected after UV irradiation. The production of gibberellic acid by mutants that had different hyphal lengths was examined in shake flasks in media with different concentrations of nutrients as well as different volumes of the medium. Fed‐batch fermenter study was performed to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…In our previous study [20], we reported on the use of morphological mutants that have short mycelial lengths in liquid cultures, which led to better oxygen transfer and increased production of GA 3 . Mor-189, used in the present investigation, is also a morphological mutant, similar to the mutants described earlier, and has the advantages of a low Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study [20], we reported on the use of morphological mutants that have short mycelial lengths in liquid cultures, which led to better oxygen transfer and increased production of GA 3 . Mor-189, used in the present investigation, is also a morphological mutant, similar to the mutants described earlier, and has the advantages of a low Fig.…”
Section: Discussionmentioning
confidence: 99%
“…An exposure time of seven seconds was found to be suitable for achieving a 95% kill rate and was used in subsequent mutagenesis experiments. In our previous study [20] we reported on mutants that were selected based on their short filament length mycelia in the fermentation broth.…”
Section: Mutagenesis and Screeningmentioning
confidence: 99%
“…For example, Lale et al obtained mutant strains with the shorter mycelium length which greatly improved the level of dissolved oxygen in the fermentation process, the yield of GA3 was nearly 2 times higher than the original strain. 22 In addition, the novel fermentation methods, such as cell immobilization and extractive fermentation techniques, were also successfully applied in the microbial production of GAs. Lu and Xie immobilized G. fujikuroi on the surface of the cellulose carrier which could continuously and efficiently produce GA3 in 84 days, the ultimate GA3 titer reached 0.21 g/L.…”
Section: Introductionmentioning
confidence: 99%
“…This GA yield exceeded most amounts reported by other researchers. Yields of 0.7 g/L using G. fujikuroi (Lale et al, 2006); 1.82 g/L by F. moniliforme (Kobomoje et al, 2013); 2.8g/L by F. moniliforme (Pastrana et al, 1993); 11.3 g/L by F. moniliforme (Bilkay et al, 2010) and 460.06 mg/L by G. fujikuroi were reported by Cuali-Alvarez et al (2011). However, higher yields of 15 g/L and 32.8 g/L have been reported by Rangaswamy (2012) and Omojasola and Benu (2016) on Jatropha seedcake using F. moniliforme and A. terreus respectively.…”
Section: Resultsmentioning
confidence: 85%